An Innovative Student Management: Exploring the Impact of Meditation Retreats and Mindful Education on Mindfulness and Compassion Effectiveness - Burmansah, Burmansah; Pembangunan, Heldy Ramadhan Putra; Suryanadi, Juni; Susanto, Susanto; Tu, Chan Phap (Jurnal Pendidikan Progresif, 2025)
An Innovative Student Management: Exploring the Impact of Meditation Retreats and Mindful Education on Mindfulness and Compassion Effectiveness Objective: This study aims to determine the effectiveness of Innovative Student Management (ISM) through the integration of meditation retreats, mindful living education, and compassion-based pedagogy in enhancing students’ mindfulness effectiveness, that defined as the ability to maintain sustained attention, emotional regulation, and awareness of thoughts and actions, and compassion, defined as the capacity for empathy and prosocial concern toward others. The research explicitly investigates how these practices influence students’ emotional regulation, empathy, and behavioural outcomes within Buddhist-based educational contexts. Methods: Using a mixed-methods design, the study combines a qualitative case study, literature synthesis, and a quantitative survey involving 120 students aged 11–17 from Buddhist schools in Palembang. Quantitative data were analyzed using multiple linear regression analysis, while qualitative data from interviews and observations were thematically analyzed to provide contextualization for the statistical results. Findings: Regression analysis showed that meditation retreats (β = 0.38, p < 0.01) and mindful living education (β = 0.42, p < 0.01) significantly predicted mindfulness effectiveness, which in turn mediated the increase in compassion (β = 0.47, p < 0.001). Qualitative findings supported these results, showing enhanced emotional awareness and peer empathy, as well as reduced impulsivity. The integration of both datasets confirmed that ISM fosters emotional regulation and prosocial behaviour while mitigating bullying tendencies. Conclusion: This study concludes that integrating mindfulness and compassion-based management in education effectively fosters students’ socio-emotional development. However, its cultural specificity and limited sample suggest the need for longitudinal, cross-cultural research and teacher training adaptations to ensure broader applicability. The findings contribute empirically to educational management theory by linking Buddhist-inspired pedagogies to measurable emotional and behavioral outcomes. Keywords: innovative student management, mindfulness in education, compassionate student, meditation retreat, mindful living education.